2014
DOI: 10.1890/13-0578.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochar amendment in a nature restoration area: effects on plant productivity and community composition

Abstract: Abstract. Biochar (pyrolyzed biomass) amendment to soils has been shown to have a multitude of positive effects, e.g., on crop yield, soil quality, nutrient cycling, and carbon sequestration. So far the majority of studies have focused on agricultural systems, typically with relatively low species diversity and annual cropping schemes. How biochar amendment affects plant communities in more complex and diverse ecosystems that can evolve over time is largely unknown. We investigated such effects in a field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 49 publications
(59 reference statements)
1
31
0
Order By: Relevance
“…Experiment I was set up in October 2010. Full details of the experimental set-up can be found in Van de Voorde et al (2014). In short, the experimental site is located on an ice pushed ridge formed during the Saalien Ice Age.…”
Section: Experimental Field Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Experiment I was set up in October 2010. Full details of the experimental set-up can be found in Van de Voorde et al (2014). In short, the experimental site is located on an ice pushed ridge formed during the Saalien Ice Age.…”
Section: Experimental Field Sitementioning
confidence: 99%
“…It was pyrolysed at 400°C or 600°C with a dwell time at this maximum temperature of 5 min (for a detailed description see: Van de Voorde et al, 2014). A portion of the unpyrolysed feedstock was shredded and air-dried before being stored in a cool dark barn.…”
Section: Biochar Production and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…litter) on plant growth. Other recent studies showed that the addition of biochar to soils can alter the composition of grassland ecosystems (Schimmelpfennig et al 2014, van de Voorde et al 2014a. Taken together, this suggests that biochar additions to soil have the potential to induce either positive or negative feedbacks on plant performance in general and therefore may also impact invasive species success.…”
Section: Introductionmentioning
confidence: 87%
“…Taken together, this suggests that biochar additions to soil have the potential to induce either positive or negative feedbacks on plant performance in general and therefore may also impact invasive species success. Additionally, understanding how biochar amendments impact invasive species growth is particularly important if soil amendments like biochar are to be used as a management tool in either agricultural (Curaqueo et al 2014) or non-agricultural grassland ecosystems (Ohsowski et al 2012, Schimmelpfennig et al 2014, van de Voorde et al 2014a. Unfortunately the impact of biochar additions on the success of invasive plants remains understudied (Adams et al 2013).…”
Section: Introductionmentioning
confidence: 99%